Hans Jonas’ principle of responsibility - de Siqueira, José Eduardo (Acta Bioethica, 2001)
This paper is a reflection on the main work of the german philosopher Hans Jonas. It shows his intellectual trajectory till the point of the rescueing of the ethics of responsibility, suggested in Max Weber’s works of the beginning of this century. Jonas’ principle of responsibility is an extremely critical analysis of modern science and its principal "armed arm", technology. The philosopher expounds the need all human beings have to act with caution and humility in face of the tremendous transforming power technoscience posseses.